2006
DOI: 10.1108/03074350610676723
|View full text |Cite
|
Sign up to set email alerts
|

Cash flow estimation practices in Mediterranean countries

Abstract: Purpose – To examine, determine, investigate and compare the extent to which enterprises in Greece and Cyprus use the theoretical framework to evaluate investments which are the discouraging factors concerning the use of this framework with particular emphasis to investigate the type, size and percentage of total capital expenditures detailed cash flow estimates; cash flow estimation practices and forecasting errors experience in the businesses in Greece and Cyprus. Design/methodology/approach – The inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…26 and 28, that are formulated by adopting the energy as a proxy for the orientation and are numerically easier to handle. As noted in INTRODUCTION, the spatially resolved energetics of water is considered to be useful for ligand design, [17][18][19][20][21][22][23][24][25][26][27][28]31,32,43 and the present work employed the DFT in the mixed representation of position and energy to elucidate which region of solvent (water) leads to stabilization or destabilization of the solute. It is thus expected that the spatialdecomposition extension of the energy-representation formalism can be a basis for addressing the role of water toward modification of ligand affinities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 and 28, that are formulated by adopting the energy as a proxy for the orientation and are numerically easier to handle. As noted in INTRODUCTION, the spatially resolved energetics of water is considered to be useful for ligand design, [17][18][19][20][21][22][23][24][25][26][27][28]31,32,43 and the present work employed the DFT in the mixed representation of position and energy to elucidate which region of solvent (water) leads to stabilization or destabilization of the solute. It is thus expected that the spatialdecomposition extension of the energy-representation formalism can be a basis for addressing the role of water toward modification of ligand affinities.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] The spatially resolved energetics receives much attention recently in connection to ligand design for proteins. [17][18][19][20][21][22][23][24][25][26][27][28] The inhomogeneous solvation theory sets a basis for investigating the energy and entropy of water molecules at the biomolecular surface, and a practical strategy has been proposed to identify the locations of water that are to be displaced by ligands possibly with improved affinities. The empirical scheme based on the accessible surface area and the method of 3D-RISM (three-dimensional reference interaction site model) can also be viewed as ones with spatial (regional) decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of small-and medium-sized Mediterranean-based companies, Lazaridis (2006) found detailed cash flow estimates to be required for almost all types of investment and a large proportion of his sample adopted standardised procedures for estimating items such as taxes, depreciation, and salvage values. Of particular note, the majority of Greek firms surveyed were found to adjust CBCFFs in order to compensate for overoptimistic biasing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Merchant 1985, Lukka 1988, Dunk 1993, Van der Stede 2000, Davila and Wouters 2005, one is struck by the scant attention directed to the potential for biasing cash flow projections in connection with capital budgeting. An extensive literature search has identified only four empirical studies that have expressly examined the issue (see Pruitt and Gitman 1987, Guilding 2003, Lazaridis 2006, Guilding and Lamminmaki 2007. None of these studies, however, sought to develop a framework concerning variables that might affect the extent of biasing of CBCFFs.…”
Section: Introductionmentioning
confidence: 96%
“…We allowed side-chain χ angles to minimize continuously within ±9° of modal χ-angles but did not model backbone flexibility. Furthermore, we did not model explicit waters, instead relying on the EEF1 implicit solvation model 76 in OSPREY. As a result, our models likely underestimate entropy and overestimate internal energy.…”
Section: Entropy Internal Energy and Helmholtz Free Energy Calculationmentioning
confidence: 99%